Espaços de Hilbert de reprodução e aproximação de soluções e equações integrais de volterra - Ferreira, Estela Costa (2016)
The aim of this study is to give the exact solution to a system of linear Volterra integral equations. So do it, we will use the theory of reproduction Kernel method and positive de nite kernels, since the usual method to solve di erential and integral equations have restrictions. Much of the study about solving equations is based on analyzing the behavior of solutions, called qualitative study. This is not our interest, we want to approach the solution of the problem using the representation of the solution in a special orthonormal basis of the reproduction kernel Hilbert space generated by an appropriate positive de nite kernel. Thus, truncating the series found for the solution of the Volterra system, we can give a good approximation to the system solution. The Volterra integral equations, focus of this work, are important to modeling physical, demographic or epidemiological phenomena. For solving such equations, we make an introductory study of linear algebra, analysis and measure theory in order to comprehend topics such as: existence of a base in a vector space, the Gram-Schmidt orthogonalization process, the spaces Lp, and others. We make a brief analysis of the Laplace transform, as well as solve a di erential and integral equation using this method. We also solve a system of integral equations by Laplace transform to illustrate the method. It should be noted that most of the equations can not be solved by means of the Laplace transform. We will study how to solve linear Volterra equations and then extend the study to nonlinear equations.